Association of As, Pb, Cr, and Zn urinary heavy metals levels with predictive indicators of cardiovascular disease and obesity in children and adolescents. (May 2022) - Nasab, Habibeh; Rajabi, Saeed; Eghbalian, Mostafa; Malakootian, Mohammad; Hashemi, Majid; Mahmoudi-Moghaddam, Hadi
Abstract: Background: Although the basic causes of obesity and cardiovascular illness have been extensively researched, little is known about the influence of environmental variables such as heavy metals on obesity development and cardiovascular disease in children and adolescents. The assumption that arsenic (As), lead (Pb), chromium (Cr), and zinc (Zn) exposure impact obesity and predictors of cardiovascular disease was explored in this study. Method: A questionnaire was used to gather demographic information as well as certain determinants of exposure to As, Pb, Cr, and Zn from 106 children and adolescents aged 6 to 18. Physical tests (height, weight, waist circumference (WC), BMI, BMI Z-score, Systolic blood pressure (SBP), Diastolic blood pressure (DBP)), blood samples for clinical trials (Fasting Blood Sugar (FBS), Total Cholesterol (TC), Triglyceride (TG), Low-Density Lipoprotein (LDL), High-Density Lipoprotein (HDL) (, and urine samples for urinary creatinine measurement and measures of As, Pb, Cr, and Zn in urine were obtained using the Inductively coupled plasma mass spectrometry (ICP/MS). Results: The average age of the participants in the research was 11.42 ± 3.68. The majority of the participants in the research were boys (56 people). As, Pb, and Zn mean concentrations (μg/L) were greater in obese adults (42.60 ± 22.59, 20.63 ± 14.64, 326 ± 164.82), respectively. After adjusting for possible confounding factors, the data revealed that adolescents aged 12–18 years had higher levels of As and Pb (8.69 and 5.02 μg/L) than children aged 6 to 11. As and Zn metals had significant association with FBS and lipid profile (TC, TG, LDL, HDL), lead had significant correlations with lipid profile, while Cr had significant correlations with WC, SBP, FBS, LDL, TC. Conclusion: Childhood and adolescent exposure to As, Pb, Cr, and Zn can impact obesity and cardiovascular disease markers. The current research was a cross-sectional study, which necessitates group studies and case studies to evaluate causal relationships. Graphical abstract: Image 1 Highlights: Urinary heavy metal concentrations of As, Pb, Cr, and Zn were measured. Relationship between heavy metals and cardiovascular disease and obesity was investigated. As and Zn metals had a significant association with FBS and lipid profile. Pb had significant correlations with lipid profile. Cr had significant correlations with WC, SBP, FBS, LDL, and TC.